Implementasi Konsep Desain Body Kit Mobil GH Style sebagai Representasi Budaya Visual Konsumen Milenial - Narhendrha Putra Sardjana; Huddiansyah Huddiansyah; Geggy Gamal (Jurnal Desain Produk Nasional, 2026)
Based on the low level of knowledge and understanding of the Product Design students, majoring in Transportation Design, in the creative process of Product Design from a Socio-Cultural Science perspective, as well as the lack of insight of the academic community regarding the breadth of alternative employment opportunities in the scope of product design in the automotive industry in Indonesia, this research was conducted with the specific aim of enriching references and teaching materials in the scope of product design education, which applies consumer lifestyle theory as one of the basic foundations when carrying out the process of creating innovative and creative product designs. The chosen research theme is to review the design of a domestic car body kit accessory called GH Style using an interdisciplinary qualitative research method with phenomenological techniques, to find its relevance to the lifestyle of the millennial generation. This research began with a review of works and literature, as well as several interview sessions with several key informants in the field of car modification that have been recognized internationally. After conducting a valid data collection process, the researcher will then review the GH Style Type 001 body kit product intended for commercial cars such as the Daihatsu Gran Max, with lifestyle theory and product design aesthetic theory, to find the relevance between Social and Cultural Sciences and Product Design Science. Therefore, it can be concluded that this research will add to the wealth of teaching materials in the Product Design group, because it has never been done before, especially for the same product.